Desingularization of Ore operators. (May 2016) - Chen, Shaoshi; Kauers, Manuel; Singer, Michael F.
Abstract: We show that Ore operators can be desingularized by calculating a least common left multiple with a random operator of appropriate order, thereby turning a heuristic used for many years in several computer algebra systems into an algorithm. Our result can be viewed as a generalization of a classical result about apparent singularities of linear differential equations.